Knowledge and attitude of universal precaution among nursing staff in a tertiary hospital of Manipur - Chaudhuri, Susmita; Baidya, Omkar Prasad; Singh, T. Gambhir (International Journal Of Community Medicine And Public Health, 2017)
Background: Health workers are exposed to blood and other body fluids in the course of their work. Successful implementation of universal precaution can effectively control these infections in health care setting. The objectives were to assess the knowledge & attitude of universal precautions among nurses in a tertiary health centre of Manipur. Methods:A cross-sectional study was conducted among the nursing staffs in a tertiary health care centre of Manipur during October 2011 to September 2013. Respondents were purposively selected and data were collected using structured questionnaire. Descriptive statistics like percentage was used to describe the findings. Results: Total respondents were 446 nurses. Response rate was 98%. Majority of the nurses i.e. 86.3% were aware of universal precaution. 61.8% of the nurses mentioned wearing gloves for contact with body fluid, non-intact skin and mucous membrane as a measure that constituted universal precaution. More than half of them knew about the personal protective equipment use and the importance of hand washing. Around 6 in 100 nurses knew that recapping should be avoided. Only 1.8% of the nurses knew about proper sharp disposal. Little was known about biomedical waste management and disposal (9.9%). 81.5% answered correctly that the aim of universal precaution is to prevent mutual transfer of infection between patients and health care workers. Eight in ten nurses (79.5%) knew correctly that all patients were a source of potentially infectious blood and body fluids. Majority of the nurses agreed that universal precaution should be applied in institutional practice (77.8%). Conclusions:Awareness and attitude were favourable. But detailed knowledge about universal precaution was little. Training of the health care workers, proper equipment supply, posters displaying guidelines and proper hospital policy of patient load management would significantly help both quantitatively and qualitatively for effective implementation of universal precaution in this premier health care institution of Manipur.